Syntactic Choices in EFL Writing: The Dynamics of Adjuncts and Complements - Herayanti, Eva; Bochari, Siska; Maf’ulah, Maf’ulah; Hastini, Hastini (e-Journal of Linguistics; Vol 19 No 2 (2025): ejl-JulyDO - 10.24843/e-jl.2025.v19.i02.p12, 2025)
The objective of this research is to find out whether adjunct or complement is the often used in EFL students’ with identifying which types of phrases functioning as adjuncts or complements pose the oftenest use for these EFL students and to find out EFL students’ difficulty factors in using adjunct and complement in writing sentences. The population for this research consisted of 5th-semester students from the English Education Study Program at Tadulako University, with 36 students from Class B selected as the sample through purposive sampling. This research used a quantitative descriptive method with statistical analysis. Data were collected using test and questionnaire. The result of the data analysis show that: (1) adjunct is the often used than complement in students’ writing, with the total frequency of 315. (2) prepositional phrase is often used as adjunct in EFL students’ sentences, comprising 71.1% of all adjunct usage. (3). an internal factor is identified as the main difficulty affecting EFL students' use of adjuncts and complements in writing sentences.